The Role of Business Administration and Entrepreneurship Education, with Government Support, in Advancing MSME Efforts Towards Achieving the SDGs - Maula, Farij; Sutomo; Setyawati, Amelia; Susantiningrum; Rahma, Adelia; Pratesa, Dimas Putri Mega; Mufidah, Eva (Economics and Business Journal (ECBIS), 2025)
In the era of competitive globalization, MSMEs face pressure to improve their performance to compete in the domestic and international markets. In Indonesia, MSMEs are expected to be the backbone of the economy towards a Golden Indonesia 2045 and the achievement of the SDGs. However, the main challenges lie in the limited insight of business administration, entrepreneurship education that has not been integrated with practice, and lack of access to government support. This research examines the role of business administration, entrepreneurship education, and government support in encouraging MSMEs in Pasuruan to upgrade. The research uses a qualitative method with a thematic analysis approach. Data were collected through in-depth interviews and observations. Data triangulation was carried out to ensure the validity of the findings. The results show that most MSME actors do not understand the importance of business administration, such as the ownership of NIB and NPWP, which are the basic requirements for accessing government programs and market expansion. Although there is a gap between the theory obtained and the practice implementation in the field, entrepreneurship education shows a fairly good level. The results of this study can be a guide for entrepreneurship education providers to design applicable practice-based programs, as well as for the government in facilitating business administration and entrepreneurial assistance. This synergy is expected to encourage Pasuruan MSMEs to upgrade, contribute to Sustainable Development (SDGs), and support the vision of Golden Indonesia 2045.